WS2 Nanorod as a Remarkable Acetone Sensor for Monitoring Work/Public Places - Rajneesh Kumar Mishra; Vipin Kumar; Le Gia Trung; Gyu Jin Choi; Jeong Won Ryu; Sagar M. Mane; Jae Cheol Shin; Pushpendra Kumar; Seung Hee Lee; Jin Seog Gwag (Sensors, 2022)
Here, we report the synthesis of the WS2 nanorods (NRs) using an eco-friendly and facile hydrothermal method for an acetone-sensing application. This study explores the acetone gas-sensing characteristics of the WS2 nanorod sensor for 5, 10, and 15 ppm concentrations at 25 °C, 50 °C, 75 °C, and 100 °C. The WS2 nanorod sensor shows the highest sensitivity of 94.5% at 100 °C for the 15 ppm acetone concentration. The WS2 nanorod sensor also reveals the outstanding selectivity of acetone compared to other gases, such as ammonia, ethanol, acetaldehyde, methanol, and xylene at 100 °C with a 15 ppm concentration. The estimated selectivity coefficient indicates that the selectivity of the WS2 nanorod acetone sensor is 7.1, 4.5, 3.7, 2.9, and 2.0 times higher than xylene, acetaldehyde, ammonia, methanol, and ethanol, respectively. In addition, the WS2 nanorod sensor also divulges remarkable stability of 98.5% during the 20 days of study. Therefore, it is concluded that the WS2 nanorod can be an excellent nanomaterial for developing acetone sensors for monitoring work/public places.